LAND DISPUTE SETTLEMENT POST LAW NO. 2 OF 2012; GLAGAH VILLAGE CASE STUDY RELATED TO NYIA AIRPORT - King Faisal Sulaiman; Iwan Satriawan (Indonesia Private Law Review, 2021)
The location for the New Yogyakarta International Airport (NYIA) construction involved in land disputes during the land acquisition process. The land acquisition will always lead to disputes or conflicts with the affected people. It is even more complicated if, in the development process, the ruling elite intervenes, external forces outside the local community that are not directly related to the development. This article deals with the question of the government's public perceptions of the legal polemic of land dispute settlement based on Law No.2 of 2012, and concentrates to examine a new model of land dispute resolution from the perspective of affected communities against NYIA. This research is normative-empirical based on primary and secondary data, namely a literature study, field study, using purposive sampling with interviews, FGD, observation, and qualitative descriptive analysis. The result showed the failure of formal litigation and non-litigation approaches offered by Law No.2 of 2012 to resolve the disputes fairly. Village discussions based on local wisdom as a new model for equitable land dispute resolution needs a political review of Law No. 2 of 2012. The new paradigm of agrarian reform must be based on customary law and local wisdom values in the 1945 Constitution and the Agrarian Law. Given recent controversies concerning land disputes, a law on reform and structuring the national agrarian structure, Agrarian conflict resolution law, and law of natural resources management for the community are urgently needed.